Self-diffusion coefficient of fe, pb, ni and Cr by molecular dynamics simulation using the potential morse. (January 2020) - Ma'nun, Luq'il; Arkundato, Artoto; Misto,; Purwandari, Endhah; Sujito,
Abstract: The molecular dynamics simulation using the Morse potential has been applied to calculate the value of self-diffusion coefficients D ( T ) of some pure metals as Pb, Cr, Ni, and Fe. The simulation then was done using the MOLDY molecular dynamics program. The procedure to calculate these coefficients following several steps: first, determining the Morse potential parameters as D, a and r 0 ; second, simulating the material under consideration using Moldy based on the appropriate ensemble; third, diffusion coefficient calculation using the Green-Kubo method for specific temperature; and fourth, the temperature-dependent diffusion coefficient D ( T ) based on the Arrhenius. The simulation work has obtained the best results as following: for Pb metal the Morse potential parameter ( a = 1.4795 A −1, r 0 = 3.733 Å, and D = 0.2348 eV ) with D ( T ) = 9.68 × 10 − 9 exp ( − 3890.79 R T ) [ m 2 / s ] ; for Cr metal the potential parameters ( D = 0.3292 eV, a = 1.1005 A −1, and r 0 = 2.2032 Å), with D ( T ) = 1.73 × 10 − 3 exp ( − 8725.54 R T ) [ m 2 / s ] ; for Ni metal the Morse potential parameter ( D = 0.3784 eV, a = 1.0649 A −1, r 0 = 2.085 Å), with D ( T ) = 8.5 × 10 − 4 exp ( − 15794.9 R T ) [ m 2 / s ] ; and for Fe metal the potential parameter ( D = 0.4174 eV, a = 1.5974 A −1, r 0 = 2.840 Å) with D ( T ) = 4.22 × 10 − 7 exp ( − 5878.49 R T ) [ m 2 / s ] . The calculated diffusion coefficients of the work have significant application as for the corrosion study of steels in nuclear reactor design.